Synthesis of highly crystalline multilayeres structures of BNNTs as a potential neutron sensing element / Pervaiz Ahmad - Pervaiz, Ahmad (2016)
We developed a simple and cost-effective Argon supported thermal CVD technique for the synthesis of h-BN nanostructures. Our developed technique for the synthesis of boron nitride nanotubes (BNNTs) is about 18 % less expensive as compared to the known simplest CVD techniques and 25 – 35 % to any other technique with respect to the cost of experimental setups and other accessories. The optimization of experimental parameters and slight modification of our Argon supported thermal CVD technique leads to the synthesis of different types, size, morphologies and shapes of h-BN nanostructures such as BNNTs, BNNWs, BNMTs and BNNS etc. Change in precursors and substrate nature resulted in different morphologies and formats of BNNTs, whereas the change of reaction atmosphere from Argon to Ammonia resulted in the synthesis of BNMTs. The decrease in the growth duration (60 min  30 min) and arrangement of vapor – liquid – solid (VLS) growth mechanism resulted in the synthesis of BNNWs, whereas an increase in the growth duration (60 min  90 min) in the presence of ammonia as a reaction atmosphere resulted in the formation of BNNS. FESEM, EDX, HR-TEM, XPS and Raman are used as characterization tools to study the morphology, size, internal structure, elemental compositions and phase of the final product, respectively. The synthesized nanostructures of h-BN have importance not only in the field of biomedical or microelectronic mechanical systems but also in the developments of solid state neutron detectors with higher detection efficiency.